The Effect of ESG Ratings on Bank Leverage Evidence From Non-Financial Sector Companies Listed on Indonesia Stock Exchange (IDX) in 2022-2024 - Jevin Meichael Chiang; Sari Indah Oktanti Sembiring (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study examines the effect of ESG ratings on bank leverage among non-financial sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. ESG ratings are measured using Bloomberg ESG scores, while bank leverage is measured as bank debt divided by total assets. Using panel data from 46 companies (138 firm-year observations), this study applies panel data regression and selects the Random Effects Model (REM) based on model selection tests. The results show that ESG ratings have a positive but statistically insignificant effect on bank leverage. These findings indicate that higher ESG ratings does not necessarily increase firms’ reliance on bank financing. The results do not support Signaling Theory but are more consistent with the view that firms with stronger ESG ratings may rely less on external debt. This study contributes to the sustainable finance literature by providing evidence from an emerging market context where bank financing remains an important source of corporate funding.